Restoring an international gold standard—A viable alternative? - Wulfdiether Zippel (Intereconomics, 1982)
The Gold Commission, whose 17 members were appointed by President Reagan in June 1981, has been conferring since autumn last year. The task of this commission is to discuss the pros and cons of restoring some gold backing for the dollar and to study the role of gold in the international economy. Prof. Zippel analyses whether an international gold standard would at all be able to operate trouble-free under present conditions.
Keywords: 330; Monetary Policy